2015
DOI: 10.1590/s0036-46652015000100010
|View full text |Cite
|
Sign up to set email alerts
|

ASSESSMENT OF THE PRESENCE OF Toxocara EGGS IN SOILS OF AN ARID AREA IN CENTRAL-WESTERN ARGENTINA

Abstract: With the aim of studying the contamination of soils with eggs of Toxocara spp. in an arid area in the central-western region of Argentina, 76 soil samples were collected from 18 towns belonging to six provinces of central-western Argentina. They were processed by the centrifugal flotation method. No eggs of Toxocara spp. were found. It can be concluded that the negative results are directly related to the characteristics of the environment and climate present in the studied area. The finding of eggs in soils d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 18 publications
0
10
0
9
Order By: Relevance
“…Most studies in Argentina showed a relationship between human seroprevalence and soil contamination, and to a lesser extent, with the prevalence found in dogs. 6,7 Therefore, a survey was performed to estimate the degree of contaminated soil by…”
Section: Introductionmentioning
confidence: 99%
“…Most studies in Argentina showed a relationship between human seroprevalence and soil contamination, and to a lesser extent, with the prevalence found in dogs. 6,7 Therefore, a survey was performed to estimate the degree of contaminated soil by…”
Section: Introductionmentioning
confidence: 99%
“…Bojanich et al (2015) avaliaram a necessidade de um consenso internacional para padronizar os métodos de amostragem do solo e processamento laboratorial, tornando os resultados mais comparáveis entre as várias pesquisas nas regiões do mundo. Guimarães et al (2005) realizaram estudo no município de Lavras, Minas Gerais, avaliando a contaminação por ovos de Toxocara spp.…”
Section: Discussionunclassified
“…Fato preocupante uma vez que esses locais são comumente compartilhados por pessoas e animais de companhia como espaços para recreação e trânsito (BOJANICH et al, 2015).…”
unclassified
“…According to literatures, environmental contamination is main root of human infection. The range of temperature, humidity and direct sunlight affect infection ability of Toxocara eggs to contaminate other hosts likewise human (13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%